Data Mining Untuk Menganalisa Pola Penjualan Pestisida dengan Mengunakan Algoritma FP-Growth - Masyuni Hutasuhut; M Gilang Suryanata; Sri Kusnasari; Muhammad Agung Lesmana (JURIKOM (Jurnal Riset Komputer), 2022)
UD. Dimas Tani is a shop located in Perbaungan District in Serdang Bedagai Regency, North Sumatra. This shop sells various types of pesticides. However, in the process of recording the data, the store still uses a manual system, so the store cannot identify and classify which pesticides have the highest sales volume. Therefore, the difficulty faced by the store is that it often runs out of stock due to high sales. In order to facilitate the UD. Dimas Tani related to the problem of determining the types of pesticides that need to be in more stock and regulating the placement of pesticides, a Data Mining program was made using the FP-Growth method as a computational method to solve the problem of determining the types of pesticides that need to be in the warehouse and arranging the placement of pesticides at UD. Dimas Tani. The result of this research is the creation of a Data Mining System that can perform a process based on the results in the form of decisions in determining the type of pesticide that needs to be in stock more and the placement of the right and accurate pesticide